Delineation of management zones with measurements of soil apparent electrical conductivity in the southeastern pampas - Peralta, Nahuel Raúl (2013)
Site-specific management demands the identification of subfield regions with homogeneous characteristics (management zones). However, determination of subfield areas is difficult because of complex correlations and spatial variability of soil properties responsible for variations in crop yields within the field. We evaluated whether apparent electrical conductivity (ECa) is a potential estimator of soil properties, and a tool for the delimitation of homogeneous zones. ECa mapping of a total of 647 ha was performed in four sites of Argentinean pampas, with two fields per site composed of several soil series. Soil properties and ECa were analyzed using principal components (PC)–stepwise regression and ANOVA. The PC–stepwise regression showed that clay, soil organic matter (SOM), cation exchange capacity (CEC) and soil gravimetric water content (θg) are key loading factors, for explaining the ECa (R 2≥0.50). In contrast, silt, sand, extract electrical conductivity (ECext), pH values and -N content were not able to explain the ECa. The ANOVA showed that ECa measurements successfully delimited three homogeneous soil zones associated with spatial distribution of clay, soil moisture, CEC, SOM content and pH. These results suggest that field-scale ECa maps have the potential to design sampling zones to implement site-specific management strategies.